Vegetative propagation an alternative technique for seedling production of Aquilaria cumingiana (Decne.) Ridl. as local livelihood initiative - Orias, Angelita B.; Parilla, Richard B. (2024)
Aquilaria cumingiana (Decne) Ridl., locally known as lapnisan in Leyte, Biliran, Samar, and Negros is one of the nine agarwood-producing tree species found in the Philippines. Agarwood is a resinous wood substance highly valued for its aromatic, religious, and medicinal uses. The global demand for agarwood is increasing, attracting investors to this lucrative business. Unfortunately, due to the high demand, agarwood-producing tree species are being heavily exploited in the wild. According to Department Administrative Order No. 2017-11, Aquilaria cumingiana is classified as Vulnerable (VU) (DENR-DAO, 2017). Therefore, conserving this species is crucial.
In response to the rapidly diminishing availability of agarwood in the wild and to satisfy market demand, much effort has been committed to agarwood production in plantations. Plantation establishment is a better option than pure agarwood collection from the wild and trade restriction. However, there is a challenge in securing the source of planting materials. Therefore, this study aims to identify the most effective and cost- efficient macro-propagation through top cutting and air-layering influenced by indole- 3-butyric acid (IBA) to achieve the highest survival rate and root development of Aquilaria cumingiana. Specifically, the study assessed the morphological growth performance and ecophysiology traits of the propagated Aquilaria cumingiana seedlings through air-layering and top cuttings; assessed the social acceptability of Aquilaria trees planted in plantations located in Leyte; and developed a feasible and doable vegetative propagation protocol for Aquilaria cumingiana that farmers could adopt to support local livelihood initiatives.
The study found that cuttings treated with 500 ppm had a relatively high survival rate (42%) and root length (20.86 mm) after 3 months from planting. Meanwhile, marcots treated with 2500 ppm had the highest success rate of rooting (24.67%) after two months from layering and a high survival rate (88%) after potting. Additionally, air layering produced bigger and taller seedlings compared to top cuttings, attributed to higher stomatal conductance and assimilation rates, resulting in significantly (p>0.05) higher biomass production. Also, it was noted that cuttings are generally more expensive than marcotted seedlings due to the need for sophisticated irrigation systems and plant propagation screenhouses. Furthermore, the cost of the root hormone (IBA) significantly increases the price of the seedlings per treatment in both propagation techniques used.
Master's thesis (M.S. Environmental Science) -- University of the Philippines, Tacloban.